Syndemics, sex and the city: understanding sexually transmitted diseases in social and cultural context. - Singer, Merrill C; Erickson, Pamela I; Badiane, Louise; Diaz, Rosemary; Ortiz, Dugeidy; Abraham, Traci; Nicolaysen, Anna Marie (Social science & medicine (1982), 2006)
This paper employs syndemics theory to explain high rates of sexually transmitted disease among inner city African American and Puerto Rican heterosexual young adults in Hartford, CT, USA. Syndemic theory helps to elucidate the tendency for multiple co-terminus and interacting epidemics to develop under conditions of health and social disparity. Based on enhanced focus group and in-depth interview data, the paper argues that respondents employed a cultural logic of risk assessment which put them at high risk for STD infection. This cultural logic was shaped by their experiences of growing up in the inner city which included: coming of age in an impoverished family, living in a broken home, experiencing domestic violence, limited expectations of the future, limited exposure to positive role models, lack of expectation of the dependency of others, and fear of intimacy.
Keywords: Adolescent; Adult; African Americans; Anthropology, Cultural; Connecticut; Culture; Decision Making; Female; Focus Groups; Hispanic Americans; Humans; Interviews as Topic; Male; Risk Assessment; Risk Factors; Sexual Behavior; Sexually Transmitted Diseases; Social Environment